Myelin basic protein binds to and inhibits the fibrillar assembly of Aβ42 in-vitro() - Hoos, Michael D. (Biochemistry, 2009)
The deposition of amyloid β-protein (Aβ) fibrils into plaques within the brain parenchyma and along cerebral blood vessels is a hallmark of Alzheimer’s disease. Aβ peptides are produced through the successive cleavage of the Aβ precursor protein by β and γ-secretase, producing peptides of between 39 and 43 amino acids in length. The most common of these are Aβ40 and Aβ42, the first of which being the most abundant. Aβ42 is more fibrillogenic than Aβ40 and has been implicated in early Aβ plaque deposition. Our previous studies determined that myelin basic protein (MBP) was capable of inhibiting fibril formation of a highly fibrillogenic Aβ peptide containing both E22Q (Dutch) and D23N (Iowa) mutations associated with familial forms of cerebral amyloid angiopathy [Hoos et al. 2007 J. Biol. Chem. 282:9952–9961]. In the present study we show through a combination of biochemical and ultrastructural techniques that MBP is also capable of inhibiting the β-sheet fibrillar assembly of the normal Aβ42 peptide. These findings suggest that MBP may play a role in regulating the deposition of Aβ42 and thereby also may regulate the early formation of amyloid plaques in Alzheimer’s disease.